2023
DOI: 10.3389/fnut.2022.904745
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the Healthy Eating Index-2015 and S-Klotho plasma levels: A cross-sectional analysis in middle-to-older aged adults

Abstract: Background and aimThe Healthy Eating Index (HEI) is a dietary index developed by the United States Department of Agriculture (USDA) to determine whether a diet adheres to US dietary guidelines. Soluble Klotho (S-Klotho) is a protein with essential anti-aging properties. However, whether HEI is linked to S-Klotho plasma levels is still debatable. This study aimed to assess the association between HEI-2015 and S-Klotho in middle-to-older aged adults in the National Health and Nutrition Examination Survey (NHANES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Abigail et al ( 44 ) emphasized a dose-dependent relationship between diet quality and both longevity and successful aging. Ma ( 45 ) revealed a positive correlation between HEI-2015 and the plasma levels of the anti-aging protein S-Klotho, suggesting a potential link between healthy eating and anti-aging attributes. Research by Fan et al ( 46 ) established a negative correlation between higher HEI-2015 scores and a reduced likelihood of physical frailty in American older individuals.…”
Section: Discussionmentioning
confidence: 97%
“…Abigail et al ( 44 ) emphasized a dose-dependent relationship between diet quality and both longevity and successful aging. Ma ( 45 ) revealed a positive correlation between HEI-2015 and the plasma levels of the anti-aging protein S-Klotho, suggesting a potential link between healthy eating and anti-aging attributes. Research by Fan et al ( 46 ) established a negative correlation between higher HEI-2015 scores and a reduced likelihood of physical frailty in American older individuals.…”
Section: Discussionmentioning
confidence: 97%
“…The present study revealed a novel mediating effect of serum α-Klotho on the relationship between a healthy dietary pattern and improved kidney function. A previous study has demonstrated a positive association between HEI-2015 score and serum α-Klotho among 8456 participants aged 40–79 years from the NHANES study [ 17 ]. A high-quality diet is related to lower serum levels of various inflammatory factors such as IL-6, IL-1β, and TGF-β, which down-regulate the expression of α-Klotho [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have demonstrated a positive correlation between serum α-Klotho levels and eGFR among adults aged 40–79 years, as well as an inverse association between serum α-Klotho levels and the prevalence of CKD [ 16 ]. Moreover, a positive association has been established between the serum α-Klotho level and adherence to a healthy diet, as indicated by HEI-2015 scores [ 17 ]. Nevertheless, the role of serum α-Klotho in the relationship between diet quality and kidney function has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…A low-calorie, high-protein diet increases klotho levels in a rat's brain, while a phosphate-restricted diet improves klotho kidney expression in a mouse model of polycystic kidney disease [45]. In a cross-sectional cohort analysis of 8456 participants (NHANES), klotho plasma levels were compared to the Healthy Eating Index-2015 (HEI) in middleto-older aged (40-79 years old) adults [46]. This index evaluates subjects' compliance with US dietary recommendations by assessing the composition and content of daily food intake [47].…”
Section: Nutritionmentioning
confidence: 99%